What are the macroeconomic effects of high-frequency uncertainty shocks - Laurent Ferrara; Pierre Guérin (Bank of Canada, 2016)
This paper evaluates the effects of high-frequency uncertainty shocks on a set of lowfrequency macroeconomic variables that are representative of the U.S. economy. Rather than estimating models at the same common low-frequency, we use recently developed econometric models, which allows us to deal with data of different sampling frequencies. We find that credit and labor market variables react the most to uncertainty shocks in that they exhibit a prolonged negative response to such shocks. When examining detailed investment sub-categories, our estimates suggest that the most irreversible investment projects are the most affected by uncertainty shocks. We also find that the responses of macroeconomic variables to uncertainty shocks are relatively similar across single- and mixed-frequency data models, suggesting that the temporal aggregation bias is not acute in this context.
Keywords: E32; E44; C32; 330; Business fluctuations and cycles; Econometric and statistical methods